Power supply system for smart contact lens - Dai, Xinyi (Nanyang Technological University, 2024)
Smart contact lenses are new wearables whose battery requirements incorporate battery characteristics with high chemical performance and biosafety to ensure steady and safe power supply. The goal of this work is to investigate the electrochemical properties of battery system that incorporates CuHCFe as the cathodic material and PB as the anodic material needed for smart contact lenses application. The structural tuning and electrochemical performance of the compounds and the entire cells in the half-cell and full-cell configurations were evaluated based on the CV and GCPL measurements. From the results presented, it is clear that the battery can only allow the smart contact lenses to operate at the performance level which is relatively steady. However, the stability becomes a major problem when the actual capacity comes below 80% of the initial true capacity for the subsequent cycles. However, the CuHCFe/PB battery might be essential in smart contact lenses, but its stability is something that needs to be boosted. More emphasis should be placed on the future research work in order to increase the cycle life, as well as the improvement of the overall capacity retention of the battery through more effective new materials or through the better choice of electrolytes. The smart contact lenses would thus be used and made famous with a constant source of power that would be paramount to the advancement of these particular devices.